2016
DOI: 10.5713/ajas.15.0842
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Swine Breeding Programs Using Genomic Selection with ZPLAN+

Abstract: The objective of this study was to evaluate the present conventional selection program of a swine nucleus farm and compare it with a new selection strategy employing genomic enhanced breeding value (GEBV) as the selection criteria. The ZPLAN+ software was employed to calculate and compare the genetic gain, total cost, return and profit of each selection strategy. The first strategy reflected the current conventional breeding program, which was a progeny test system (CS). The second strategy was a selection sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Under a genomic selection approach, Jiao et al (2014) working with Duroc pigs reported the heritability estimated obtained through Bayes A equal to 0.32 (0.09). Lopez et al (2016) reported heritability estimates for FCR closest to 0.30, and concluded that genomic selection for FCR is clearly superior to the conventional scheme in terms of monetary genetic gain and profit. According to Akanno et al (2013), when using genomic selection for feed conversion in pigs assuming heritability equal to 0.32, the accuracy of selection index ranged from 0.38 to 0.66, whereas the conventional selection provides accuracies between 0.10 and 0.64.…”
Section: Heritability Estimatesmentioning
confidence: 99%
“…Under a genomic selection approach, Jiao et al (2014) working with Duroc pigs reported the heritability estimated obtained through Bayes A equal to 0.32 (0.09). Lopez et al (2016) reported heritability estimates for FCR closest to 0.30, and concluded that genomic selection for FCR is clearly superior to the conventional scheme in terms of monetary genetic gain and profit. According to Akanno et al (2013), when using genomic selection for feed conversion in pigs assuming heritability equal to 0.32, the accuracy of selection index ranged from 0.38 to 0.66, whereas the conventional selection provides accuracies between 0.10 and 0.64.…”
Section: Heritability Estimatesmentioning
confidence: 99%
“…The inclusion of genomic evaluation in the system implies additional costs incurred by the business. In this regard, there are a number of questions about the economic feasibility of implementing such a method [23,24]. Since genomic prediction is an addition to the conventional assessment of breeding value, it is necessary to plan in advance the payback period of obtaining animals' genomic data (sample collection, genotyping and data processing) and reference population size needed for sufficient assessment accuracy and effectiveness of genomic prediction for traits due to reference population size.…”
Section: Introductionmentioning
confidence: 99%
“…The 3 layers are represented by the nucleus layer which include high-quality purebred animals, the multiplier level at which purebred animals from different lines are multiplied and crossed to obtain the F1 crossbred animals, and the production (commercial) level, at which F1 sows are crossed with purebred sires, the progeny of these crosses being used for pork production. Selection takes place at the nucleus and partially at the multiplier levels ( Visscher et al, 2000 ; Lopes, 2016 ; Lopez et al, 2016 ). The use of breeding programs of this kind leads to a certain genetic improvement lag, which is the time taken for genetic improvements achieved in the higher layer to reach the next layers ( Bichard, 1971 ; See, 1995 ), between the nucleus level at which selection and testing mostly occurs and the commercial level at which terminal (slaughter) hybrids are produced which should have the desired qualities.…”
Section: Introductionmentioning
confidence: 99%